PERANCANGAN DAN PENGEMBANGAN WEBSITE SMK PGRI 2 JOMBANG SEBAGAI MEDIA INFORMASI PROGRAM SEKOLAH - titasari rahmawati; Restu Hendriyani Magh'firoh (Universitas Bengkulu, 2020)
School is a medium or place for students to gain knowledge. So schools must provide good services to students, teachers and other staff. Services to students are not only services in academic matters that can support the success of students in the future. Information services that are accurate, current and fast are the demands of every public service today. So that SMK PGRI 2 Jombang as a Vocational School in the middle of Jombang has the same expectations as other schools that provide information quickly, accurately and always up to date. The information referred to is information about job vacancies. Currently, SMK PGRI 2 Jombang requires a website that can provide job information to all students. This website is expected by SMK PGRI 2 Jombang to assist the Job Vacancy Unit (BLK) in recording students who take the test at an institution that opens a vacancy. Because so far the BLK unit only records in Microsoft Excel, even though the number of students who are allowed to register is in the hundreds and the BLK unit consists of only 2 people. With the development of the website, it is expected to be able to help the BLK unit in selecting students who have qualifications in accordance with the requirements of the existing agencies.